2014
DOI: 10.3389/fmicb.2014.00004
|View full text |Cite
|
Sign up to set email alerts
|

Potential of known and short prokaryotic protein motifs as a basis for novel peptide-based antibacterial therapeutics: a computational survey

Abstract: Short linear motifs (SLiMs) are functional stretches of protein sequence that are of crucial importance for numerous biological processes by mediating protein–protein interactions. These motifs often comprise peptides of less than 10 amino acids that modulate protein–protein interactions. While well-characterized in eukaryotic intracellular signaling, their role in prokaryotic signaling is less well-understood. We surveyed the distribution of known motifs in prokaryotic extracellular and virulence proteins acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…This finding strengthens the suggestion on the possibility of SPD_1333 to be a membrane protein because dilysine motif plays a role in conferring the localization of this kind of protein [40]. Many types of motifs, including the dilysine motif, are known to mimic eukaryotic motifs, thus enabling pathogenic bacteria to disturb host's cellular functions [41]. From this, it is suggested that the ability of SPD_1333 to bind with dilysine motifcontaining molecule may give benefit to this protein in accomplishing its virulence mission inside the host.…”
Section: Potential Drug Design Candidatessupporting
confidence: 86%
“…This finding strengthens the suggestion on the possibility of SPD_1333 to be a membrane protein because dilysine motif plays a role in conferring the localization of this kind of protein [40]. Many types of motifs, including the dilysine motif, are known to mimic eukaryotic motifs, thus enabling pathogenic bacteria to disturb host's cellular functions [41]. From this, it is suggested that the ability of SPD_1333 to bind with dilysine motifcontaining molecule may give benefit to this protein in accomplishing its virulence mission inside the host.…”
Section: Potential Drug Design Candidatessupporting
confidence: 86%
“…There are two classes of NLS, monopartite and Bipartite. In S4TE 2.0, the search for monopartite NLS has been improved according to Ruhanen et al [6]. We rewrote this module to add more known NLS motifs in the search.…”
Section: Software and Algorithmmentioning
confidence: 99%
“…IPIO effector or some proteins/peptides with an RGD motif interact with adhesion between cell wall and plasma membrane leading to disruption of plant cells. The motifs composed of less than 10 amino acids, called short linear motifs (SliMs) enable pathogenic bacteria to control intracellular process of host [51]. The cell wall peptidoglycan of Gram positive bacteria act as surface organelle for transport and assembly of many proteins which interact with hosts.…”
Section: Targeting Of Effectors To Host Cell Role Of Conserved Motifsmentioning
confidence: 99%